2013
DOI: 10.1179/2047971913y.0000000037
|View full text |Cite
|
Sign up to set email alerts
|

Nurse retention in rural United States: A cluster analytic approach

Abstract: This study explores the factors that influence a nurse's choice to continue working in a rural area as compared to those working or commuting to urban areas. The current and predicted nursing shortage tends to have disproportionate effects in rural areas. An understanding of how nurses make the choice of which type of environment to work in is critical to addressing this shortage. A comprehensive literature review suggested a number of factors worthy of investigation, and these were assessed through six focus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…These hospitals play important roles in increasing the number of nurses in the workforce. However, there are large gaps in payment among hospitals and poor nursing work environments in small-and medium-sized hospitals; these factors are highly associated with nurse turnover (Dotson et al, 2012;Park & Ko, 2020). Considering that estimated turnover costs range from 0.75 to 2 times the annual salary of the individual (Jones & Gates, 2007), motivating nurses by providing monetary incentives as well as nonmonetary support is critical.…”
Section: Discussionmentioning
confidence: 99%
“…These hospitals play important roles in increasing the number of nurses in the workforce. However, there are large gaps in payment among hospitals and poor nursing work environments in small-and medium-sized hospitals; these factors are highly associated with nurse turnover (Dotson et al, 2012;Park & Ko, 2020). Considering that estimated turnover costs range from 0.75 to 2 times the annual salary of the individual (Jones & Gates, 2007), motivating nurses by providing monetary incentives as well as nonmonetary support is critical.…”
Section: Discussionmentioning
confidence: 99%
“…Dotson, Dave, Cazier, and McLeod () found that motivation intrinsically includes the elements of competence, self‐determination, interest, excitement, curiosity, excitement, and high levels of task involvement, all of which can be influenced by internal and external forces in the workplace. Their study found that increased motivation could bring improvements in work performance and satisfaction, which also contribute to better retention.…”
Section: Introductionmentioning
confidence: 99%
“…For example, recruiting and retaining professional nurses has always been more challenging in rural areas, especially in more remote areas and underserved regions of the world (Dieleman et al, ; World Health Organization, ). Additionally, compared to urban areas, rural healthcare facilities experience higher rates of nursing shortages along with greater challenges in retaining staff (Dotson et al, ). Internationally, nurses migrating from developing nations to industrialized countries further perpetuates nursing shortages in already underserved regions of the world.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses employed in rural hospitals are often required to take on additional, unplanned responsibilities, new or expanded roles and work across various clinical areas such as emergency, medical, maternity and mental health (Schlairet, 2017). This diversity and complexity of clinical practice is why rural nurses are often referred to as "expert generalists" and requires nurses to have a strong theoretical and practical knowledge base (Dotson, Dave, Cazier, & McLeod, 2013;Kenny & Duckett, 2003;Knight, Kenny, & Endacott, 2016). Rural nurses often work within a broad scope of practice and often work independently or with limited backup which can contribute to a heavy and potentially stressful workload (Dotson et al, 2013;Hunsberger et al, 2009).…”
mentioning
confidence: 99%